Efeito da fadiga mental, da estimulação cerebral e da associação de ambas no desempenho físico e em variáveis psicofisiológicas durante atividades aeróbicas prolongadas - Eduardo Macedo Penna (2019)
Mental fatigue is a psychobiological state characterized by impairments in cognitive performance and can be triggered by prolonged periods of high cognitive demand tasks. It has been shown that MF is also capable of reducing physical performance, mainly through the change in perceptual variables linked to human performance. To counteract the possible deleterious effect of MF on physical performance, several interventions have been proposed, which may be chronic or acute. Among them, the cerebral stimulation, which is able to reduce perceptual variables during prolonged physical or cognitive task stands out. The aim of this thesis was to establish relations between brain stimulation, through transcranial direct current stimulation, and mental fatigue. In a series of 3 experiments, athletes and untrained individuals were exposed to a protocol of mental fatigue and brain stimulation in different areas with the objective of testing whether mental fatigue affects performance in these different populations, and if brain stimulation of different areas is capable of counteracts the deleterious effect caused by MF. Furthermore, whether brain stimulation in different areas is capable of improving performance in these populations. In study 1 it was identified that mental fatigue was able to reduce performance in young swimming athletes. In study 2, the same effect was not observed in master’s athletes, and no positive effect on Temporal Cortex cerebral stimulation in physical performance was identified. However, after a qualitative approach, athletes reported a higher difficulty in staying focused during the test when mentally fatigued, which had repercussions on other psychological and behavioral variables, and that the ability to self-motivate throughout the swimming performance was important to maintain the performance level. In study 3, MF was also unable to alter the performance of untrained individuals, and brain stimulation of both the prefrontal cortex and the primary motor cortex was not effective in improving performance nor improving perceptual responses over performance. Discussions regarding the specificity of the population most vulnerable to the deleterious effects of MF, as well as the positive effects of brain stimulation (in their different cortical regions), were developed. It is concluded that mental fatigue is capable of altering the performance of specific populations and that it is probably related to perceptual alterations, mainly related to the decrease of the capacity of concentration throughout the test. Similarly, brain stimulation may be able to alter the performance of specific populations, and that this alteration also seems to be linked to the stimulation of specific areas of the cerebral cortex.